2005
DOI: 10.1007/s10535-005-0007-8
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod affects the growth and development of yam plantlets obtained by in vitro propagation

Abstract: The effects of photoperiod on the development of in vitro grown plantlets of yam (Dioscorea alata L.), were investigated. Plantlets were transplanted into pots, acclimatizated until they reached vegetative stages V 1 (3 leaves) or V 2 (8 leaves), and then grown under 12-h or 16-h photoperiod. The formation and development of underground tubers was only induced under 12-h photoperiod. Tuber initiation was not related to the initial vegetative stage of plants, and the tubers were visible at about 18 -24 d. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 17 publications
1
16
0
3
Order By: Relevance
“…Traditionally, D. candidum genetic resources are preserved as whole plants either in field repositories or maintained in greenhouses (Wang and Liu 2006). For both means, preserved plants are subject to risk of loss caused by biological and climatic hazards as well as due to human error by mislabeling samples (Vaillant et al 2005). In addition, traditional maintenance of plant material is highly costly (Wu and Tang 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, D. candidum genetic resources are preserved as whole plants either in field repositories or maintained in greenhouses (Wang and Liu 2006). For both means, preserved plants are subject to risk of loss caused by biological and climatic hazards as well as due to human error by mislabeling samples (Vaillant et al 2005). In addition, traditional maintenance of plant material is highly costly (Wu and Tang 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Al estudiar la respuesta en campo de plantas in vitro de D. alata clon 'Caraqueño' en distintos momentos de plantación en campo, Borges et al (2015) determinaron que el mayor desarrollo vegetativo significativo de la planta se alcanzó a los cuatro meses de cultivo (junio-septiembre), debido a que a partir de este momento se inicia el proceso de tuberización (septiembre). En este aspecto, Vaillant et al (2005) informaron que la tuberización en D. alata se produce doce semanas (tres meses) después del inicio de la brotación de las plantas, lo cual ha sido revelado a partir de estudios sobre el efecto del fotoperíodo en el desarrollo vegetativo de este cultivo.…”
Section: Diámetro Del Tallounclassified
“…Many research studies (Economou and Reed 1987) have shown that its variation can influence the growth of the cultures to a greater or lesser degree depending on the genotype: some species benefit from longer photoperiods, others from shorter photoperiods and still others appear to be indifferent. Photoperiod has also shown to influence plant growth during acclimatization stage (Vaillant et al 2005).…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%